Why Liberals Should Chuck the Exclusionary Rule - Slobogin, Christopher (1999)
This article makes the case against the exclusionary rule from a liberal perspective. Moving beyond the inconclusive empirical data on the efficacy of the rule, it uses behavioral and motivational theory to demonstrate why the rule is structurally unable to deter individual police officers from performing most unconstitutional searches and seizures. It also argues, contrary to liberal dogma, that the rule is poor at promoting Fourth Amendment values at the systemic, departmental level. Finally, the article contends that the rule stultifies liberal interpretation of the Fourth Amendment, in large part because of judicial heuristics that grow out of constant exposure to litigants with dirty hands. It also explains why noninstrumental justifications for the rule, even when viewed from a liberal bias, fail to support a broad policy of exclusion. In place of the exclusionary rule, the article proposes an administrative damages regime in which actions for Fourth Amendment violations would be brought directly against police officers and departments. The proposed regime includes: (1) liquidated damages for all constitutional violations, (2) personal liability for officers who knowingly or recklessly violate the Fourth Amendment, (3) departmental liability for all other violations, (4) state-paid legal assistance for all Fourth Amendment claims, and (5) a judicial decisionmaker. The article demonstrates how this regime would be superior to the exclusionary rule not only in deterring individual Fourth Amendment violations, but also in encouraging use of warrants, invigorating judicial review, diminishing racism on the beat, curbing perjury, improving hiring and training practices, and promoting respect for the system